Claude Debussy’s La Cathedrale Engloutie and Claude Monet’s La Parliament; the correlation between two form of arts during the impressionism era / Siti Lina Mastura Zulrani - Zulrani, Siti Lina Mastura (Faculty of Music, 2009)
In the 20th century, there are many divisions of eras that vastly expand into many different schools of thought. Artists are open to options in creating different approaches, techniques in performing and injecting their thoughts into their writings, this goes to the composers. Thus the existence of expressionism, minimalism, and all other divisions of artists in the respected areas are born and mould. Impressionism was one of it. During this era, it was known for a fact that many artists, routed from musicians, painters, literates, sculptors and many others are linked and connected towards one another. Their art-making ideas are inspired and correlate with one another. Thus, during this era, musicians are mostly linked with painters and vice versa.